ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA INDUSTRI KERAJINAN DI KABUPATEN SITUBONDO - Karnadi, Karnadi; Anggraini, Yunita Merdiana (Relawan Jurnal Indonesia, 2023)
The purpose of this study is to analyze the effect of the variables Role of Leadership and Work Experience on The Craft Industry In Situbondo District Regency with Job Satisfaction as an Intervening Variable by using the Partial Least Square (PLS) structural equation model. The results of the direct effect hypothesis test using the Smart PLS 3.0 application. Leadership has a significant positive effect on job satisfaction (H1 is accepted), work experience has a significant positive effect on job satisfaction (H2 is accepted), leadership has a significant positive effect on Employees performance (H3 is accepted), work experience has a positive but not significant effect on Employee performance (H4 is rejected ), Job satisfaction has a significant positive effect on Employee performance (H5 is accepted), Leadership has a significant positive effect on Employee performance through job satisfaction (H6 is accepted), and work experience has a positive but not significant effect on Employee performance through job satisfaction (H7 is rejected).